e-agriculture strategies: the case of Ivory Coast - Lohento, Ken; Speer, Mark (Technical Centre for Agricultural and Rural Cooperation, 2013)
Many African countries have developed national e-governance, e-health and e-education strategies, yet many still lack an e-agriculture strategy. One exception is Ivory Coast, which has just started to develop an e-agriculture strategy.